ENDODONTIC SURGERY: A REVIEW OF POSTOPERATIVE AND HEALING OUTCOME - Landim Gomes, Lais; Dutra, Jafar César (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2021)
The purpose of this review was to give the reader an update about the postoperative period and healing outcome after surgical endodontic retreatment. Endodontic surgery has become a standard of care for dental maintenance if conventional endodontic retreatment is not able to eliminate the infection, it is important to know how to manage the post-surgical care, due it might directly interfere in the healing outcome after the surgical procedure. An electronic search of the relevant English-language literature was conducted in the MEDLINE/ PubMed database using the following key-words combinations: Postoperative care; apical surgery; apicoectomy; wound healing. Articles from 1980 to 2011 were included. Based on the results of this present review, the postoperative period after the surgery treatment is very mild, without any complications, being similar to any dental surgical discomfort, as swelling, bleeding and pain, which could be easily controlled with simple medicine. Regarding the repair after endodontic surgery, the length of follow-up time and the healing evaluation criteria affect the outcome, and 1-year follow-up periods might be insufficient to predict a long-term healing.